The Contrast Portrayals of American and Pakistani Culture in The Big Sick Movie - Nidia Nikita; Ranti Andela; Ghina Zahra Fauziah; Zhia Aulia Nazafi (Insaniyat : Journal of Islam and Humanities, 2019)
This study aims to describe the cultural stereotypes between American and Pakistani that are portrayed in The Big Sick (2017) movie. This study uses a qualitative method with a Cultural Studies approach. The analysis is done by looking at the characteristics of American and Pakistani characters by using the theory of characterization from Boggs and the theory of representation by Stuart Hall to present the cultural stereotype issues that appear in the movie (Hall, 1997). The cultural stereotype of the American and Pakistani culture is presented by some American characters (Emily and her family) and some Pakistani characters (Kumail and his family) of The Big Sick movie. The result of the study shows that the characteristics of Pakistani characters are religious and deceitful, while the characteristics of American characters are smart and straightforward. Furthermore, through the analysis of the characters’ characteristics, the writers found the cultural stereotype in the movie. Pakistani characters are associated with conservatism and close-mindedness. On the contrary, American characters are associated with modernism and open-mindedness. It can be concluded that in this movie, American culture is depicted as more positive than Pakistani.